Assessing emotional and social competence in primary school and early years settings - Edmunds, L; Stewart-Brown, S (Department for Education and Skills, 2003)
Emotional and social competence are widely recognised as important for educational achievement and for life long learning (National Commission on Education, 1993; Ball, 1994; DfEE, 1997; DfES, 1998) There is increasing concern among those working in education to identify ways of supporting these aspects of development.